Nutritional Supplements in the Prevention of Age-Related Retinal Pathology - M. H. Durzhinskaya; M. V. Budzinskaya (Oftalʹmologiâ)
Oxidative stress due to the imbalance in the production and detoxification of reactive oxygen species in antioxidant defence system of the body, as well as subsequent chronic inflammation, is believed to be associated with age-related eye diseases. Prevention of chronic degenerative diseases such as age-related macular degeneration (AMD) and primary open-angle glaucoma are of particular interest. In the last decade, tremendous success has been achieved in the treatment of age-related retinal pathology. However, these treatments are expensive and require frequent monitoring and, in some cases, injections, which place a huge burden on both the healthcare system and patients. Consequently, considerable interest remains in preventing or slowing the progression of these diseases. Epidemiological studies have shown that diet is a modifiable risk factor for AMD, and nutritional modification with food antioxidant supplements is a particularly attractive method of prevention because of its potential benefits and relatively low cost. A large number of experimental studies, including clinical studies in animals and humans, have provided supporting evidence that antioxidant food additives inhibit the oxidation of macromolecules, as well as an inflammatory response that occurs in the pathogenesis of involutional retinal pathology, which ultimately inhibits its development and progression. This review discusses the role of antioxidant dietary supplements in the prevention of age-related retinal pathology.